Avaliação do potencial de reuso agrícola do efluente de uma estação de tratamento de esgoto com alagados construídos - Giafferis, Giselda Passos [UNESP]; Barros, Zacarias Xavier de [UNESP]; Oliveira, Eduardo Luiz de [UNESP] (EIA Energy in Agriculture, 2014)
The study took place in a sewage treatment plant located at the actual Department of Water and Sewer in Bauru, city of Sao Paulo state. This treatment plant has an average entrance flow of 4.8 l. s-1 made by upflow anaerobic filter, followed by wetland systems constructed in parallel. . As objective of this study we evaluate the effectiveness of three systems of constructed wetlands, with three different types of plants (Lily pond, Giant papyrus and Cattail),quantify, and qualify the effluents at various stages of treatment to monitor their effectiveness and the possibility of reuse in agriculture. There was a satisfactory removal of organic matter, with a mean concentration of 36 and 39mg.l-1 at the , phases 1 and 2 of the operation, respectively. The constructed wetlands effluent nitrogen and phosphate concentrations were high throughout all the system and the removal efficiency of ammonia nitrogen was much lower than expected, then the system is functioning as secondary treatment and not as tertiary treatment. The concentrations of micro-organisms found in the final effluent were also high. Therefore, it is concluded that the results of removal efficiency of organic matter, of constructed wetland systems, meet the parameters required by legislation for effluent discharges but do not attend the parameters required for nitrogen and micro organisms. This way, these analyzed plants effluents are suitable for reuse in agriculture restricted irrigation

A pesquisa foi realizada na estação de tratamento do Departamento de Água e Esgoto de Bauru, localizada no Distrito de Tibiriçá, com vazão média na entrada da estação de 4,8L/s, composta por filtro anaeróbio de fluxo ascendente, seguido de sistemas de alagados construídos em paralelo. Como objetivo deste trabalho, avaliou-se a eficiência dos três sistemas de alagados construídos, com tipos de plantas diferentes (Lírio do charco, Papiro gigante e Taboa) e analisou-se quantitativa e qualitativamente, os efluentes nas várias etapas do processo de tratamento, para verificar suas eficiências e a possibilidade de reuso do efluente final na agricultura. Diante dos resultados obtidos, observou-se que houve satisfatória remoção de matéria orgânica, com concentração média de 36 e 39 mg/L, nas Fases 1 e 2 de operação, respectivamente. Constatou-se que as concentrações de nutrientes, como nitrogênio e fosfato foram altas em todo o sistema e a eficiência de remoção de nitrogênio amoniacal esteve muito abaixo do esperado, concluindo que o sistema de alagados está funcionando como tratamento secundário e não como terciário. As concentrações de micro-organismos encontrados no efluente final foram elevadas. Portanto, conclui-se que os resultados de eficiência de remoção da matéria orgânica, dos sistemas de alagados construídos atendem aos parâmetros exigidos pelas legislações para lançamentos de efluentes e não atendem para nitrogênio e micro-organismos, mas se adequam para fins de reuso na irrigação restrita na agricultura.
Evaluation of the agricultural reuse potential of a sewage treatment plant built with constructed wetlands effluent
Keywords: Constructed wetlands; Wetlands; Sewage treatment; Reuse; Alagados construídos; Tratamento de esgoto; Wetland Construídos; Reuso de água